Lapsus calami and irony: On gender stereotypes in Carmen Martel’s La Estrella de rubíes - Sevilla-Vallejo, Santiago (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The feminine identity has been dominated by a stereotype that impoverishes it, but the masculine identity has also been stereotyped in a complementary way. Carmen Martel’s La estrella de rubíes presents a series of signs that seem to go veiled against the passive image of women and the active image of men. In this work, the psychological, historical and literary reasons for stereotypes in literature in general, and specifically in children’s adventure stories are studied. Likewise, a psycho critical study of the “lapsus calami” and the ironies that reduce the nobility of male characters and enhance the character of Belica is made. It is concluded that, although La estrella de rubíes most of the time presents a conservative image that allowed its acceptance, also offers a gender claim that can be read between the lines.